Effect of Antrodia camphorata on Inflammatory Arterial Thrombosis-Mediated Platelet Activation: The Pivotal Role of Protein Kinase C. (14th October 2014) - Lu, Wan-Jung; Lin, Shih-Chang; Lan, Chang-Chou; Lee, Tzu-Yin; Hsia, Chih-Hsuan; Huang, Yung-Kai; Lee, Hsiu-Chuan; Sheu, Joen-Rong
Abstract : Antrodia camphorata is a rare Taiwanese medicinal mushroom. Antrodia camphorata extract has been reported to exhibit antioxidant, anti-inflammation, antimetastasis, and anticancer activities and plays a role in liver fibrosis, vasorelaxation, and immunomodulation. Critical vascular inflammation leads to vascular dysfunction and cardiovascular diseases, including abdominal aortic aneurysms, hypertension, and atherosclerosis. Platelet activation plays a crucial role in intravascular thrombosis, which is involved in a wide variety of cardiovascular diseases. However, the effect of Antrodia camphorata on platelet activation remains unclear. We examined the effects of Antrodia camphorata on platelet activation. In the present study, Antrodia camphorata treatment (56–224 μ g/mL) inhibited platelet aggregation induced by collagen, but not U46619, an analogue of thromboxane A2, thrombin, and arachidonic acid. Antrodia camphorata inhibited collagen-induced calcium (Ca 2 + ) mobilization and phosphorylation of protein kinase C (PKC) and Akt. In addition, Antrodia camphorata significantly reduced the aggregation and phosphorylation of PKC in phorbol-12, 13-dibutyrate (PDBu) activated platelets. In conclusion, Antrodia camphorata may inhibit platelet activation by inhibiting of Ca 2 + and PKC cascade and the Akt pathway. Our study suggests that Antrodia camphorata may be a potential therapeutic agent for preventing or treating thromboembolic disorders.